2008
DOI: 10.1158/1535-7163.mct-07-2383
|View full text |Cite
|
Sign up to set email alerts
|

DNA vaccination with CD44 variant isoform reduces mammary tumor local growth and lung metastasis

Abstract: We have shown recently that cDNA vaccination, using a virtual lymph node, ameliorates experimental allergic encephalomyelitis. Successful cure from mammary tumor requires resolution of local tumor growth and metastases. We have examined whether targeting of CD44 cell surface adhesion molecule by cDNA vaccination plays a role in resolving mammary tumor development. We show here that CD44 cDNA vaccination decreases the tumor mass and metastatic potential in experimental mammary tumor of BALB/c mice. Vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Moreover, CD44 was used as a therapeutic target for the treatment of different cancers; gene vaccination with CD44 variant constructs [51] or injection of anti-CD44 monoclonal antibodies [52,53] were used in order to successfully control cell dissemination and achieve therapeutic effects. However, there are some oppositional observations, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CD44 was used as a therapeutic target for the treatment of different cancers; gene vaccination with CD44 variant constructs [51] or injection of anti-CD44 monoclonal antibodies [52,53] were used in order to successfully control cell dissemination and achieve therapeutic effects. However, there are some oppositional observations, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although CD44 was first described as a key regulator of cell adhesion, it is now widely accepted that its engagement activates signaling cascades involved in cell proliferation, survival, and migration. 45,46 Godar et al 35 effectively showed that CD44 is fundamental for the proliferation of tumorigenic mammary epithelial cells and demonstrated that its expression is directly inhibited by the tumor suppressor p53, a master regulator of cell proliferation. The investigators showed that, by binding to a noncanonical p53-binding sequence in the CD44 promoter, p53 inhibits CD44 expression and down-regulates the growth-promoting cascade downstream of CD44.…”
Section: Discussionmentioning
confidence: 99%
“…28 Moreover, tumors expressing the CD44 splice variant CD44v4-10 showed significantly more metastases, as well as larger primary tumors, than tumors expressing nonspliced standard CD44 in vivo. 29 But what is the actual biological relevance of the oncogenic effects of tumor-associated splice variants defined in experimental models? This is indeed an unresolved issue.…”
Section: Do Splice Variants Contribute To Malignancy?mentioning
confidence: 99%
“…For instance, in a mouse model of mammary adenocarcinoma, active immunization with a cancer-associated CD44 splice variant resulted in significantly reduced tumor growth. 29 As for the therapeutic inhibition of splice variant effects on important tumor cell functions, such as apoptosis, the main approach has been to decrease splice variant synthesis (reviewed by Garcia-Blanco 42 ), whereas pharmaceutical antagonism of splice variant functions has been less explored in cancer. The expression of a splice variant may be specifically inhibited with an oligonucleotide interfering with splice site choice.…”
Section: Splice Variant-targeted Tumor Therapymentioning
confidence: 99%